Mitochondrial fusion protein: a new therapeutic target for lung injury diseases - Jia, Guiyang; Song, Erqin; Huang, Qianxia; Chen, Miao; Liu, Guoyue (Frontiers in Physiology, 2025)
Mitochondria are essential organelles responsible for cellular energy supply. The maintenance of mitochondrial structure and function relies heavily on quality control systems, including biogenesis, fission, and fusion. Mitochondrial fusion refers to the interconnection of two similar mitochondria, facilitating the exchange of mitochondrial DNA, metabolic substrates, proteins, and other components. This process is crucial for rescuing damaged mitochondria and maintaining their normal function. In mammals, mitochondrial fusion involves two sequential steps: outer membrane fusion, regulated by mitofusin 1 and 2 (MFN1/2), and inner membrane fusion, mediated by optic atrophy 1 (OPA1). Dysfunction in mitochondrial fusion has been implicated in the development of various acute and chronic lung injuries. Regulating mitochondrial fusion, maintaining mitochondrial dynamics, and improving mitochondrial function are effective strategies for mitigating lung tissue and cellular damage. This study reviews the expression and regulatory mechanisms of mitochondrial fusion proteins in lung injuries of different etiologies, explores their relationship with lung injury diseases, and offers a theoretical foundation for developing novel therapeutic approaches targeting mitochondrial fusion proteins in lung injury.